Combination of thalidomide and Clostridium butyricum relieves chemotherapy-induced nausea and vomiting via gut microbiota and vagus nerve activity modulation - Zhao, Xuanqi; Wu, Heng; Zhu, Ruizhe; Shang, Gaishuang; Wei, Jing; Shang, Haitao; Tian, Puyuan; Chen, Tingtao; Wei, Hong (Frontiers in Immunology, 2023)
Nausea and vomiting (CINV) are distressful and widespread side effects of chemotherapy, and additional efficient regimens to alleviate CINV are urgently needed. In the present study, colorectal cancer (CRC) mice model induced by Azoxymethane (AOM)/ Dextran Sodium Sulfate (DSS) was employed to evaluate the cancer suppression and CINV amelioration effect of the combination of thalidomide (THD) and Clostridium butyricum. Our results suggested that the combination of THD and C. butyricum abundantly enhanced the anticancer effect of cisplatin via activating the caspase-3 apoptosis pathway, and also ameliorated CINV via inhibiting the neurotransmitter (e.g., 5-HT and tachykinin 1) and its receptor (e.g., 5-HT3R and NK-1R) in brain and colon. Additionally, the combination of THD and C. butyricum reversed the gut dysbacteriosis in CRC mice by increasing the abundance of Clostridium, Lactobacillus, Bifidobacterium, and Ruminococcus at the genus level, and also led to increased expression of occludin and Trek1 in the colon, while decreased expression of TLR4, MyD88, NF-κB, and HDAC1, as well as the mRNA level of IL-6, IL-1β, and TNF-α. In all, these results suggest that the combination of THD and C. butyricum had good efficacy in enhancing cancer treatments and ameliorating CINV, which thus provides a more effective strategy for the treatment of CRC.